Associated Effects of Meaning in Life and Social Adjustment Among Chinese Undergraduate Students With Left-Behind Experiences in the Post-epidemic Period - Ge, Ying; Shuai, Mei-Qiong; Luo, Jie; Wenger, Jay L.; Lu, Cun-Yang (Frontiers in Psychiatry, 2021)
Background The outbreak of COVID-19 has brought about radical changes in social life. The study focuses on a special group, Chinese undergraduate students with left-behind experiences. Specifically, the study addresses how such students feel and grasp the meaning in life and how they adapt to the current social environment after experiencing the impermanence of life. The correlation between the meaning in life and social adjustment in the post-epidemic period is evaluated. Methods The Meaning in Life Scale and the Social Adjustment Scale were used to test 988 undergraduate students. Multi-factor analysis, correlation, regression, and dominance analysis were performed on the test results. Results (1) During the epidemic, Chinese undergraduate students generally had low meaning in life scores, including below-average values for life goals, and middle-range scores for social adjustment. (2) Having or not having left-behind experiences had an important influence on the meaning in life and social adjustment of undergraduates: undergraduates with left-behind experiences performed better than those without left-behind experiences in terms of meaning in life, while their social adjustment was weaker than those without left-behind experiences. (3) The zest for life and freedom of life of undergraduates in both groups negatively predicted social adjustment, and zest for life preferentially influenced social adjustment. Zest for life also had a significant effect on life value in the group without left-behind experiences. Zest for life was a priority factor influencing social adjustment. Conclusion The epidemic and left-behind experiences are important factors influencing the relationship between meaning in life and social adjustment among Chinese undergraduate students.